Efektivitas Proses Program Studio EL-TV Balai Diklat Keagamaan Palembang - Hamandia, Muhammad Randicha; Hertimi, Sri; Rais, Wirdiyan (Indonesian Journal Publisher, 2025)
This study aims to evaluate the effectiveness of the Studio eL-TV program process at the Palembang Religious Training Center as an audiovisual-based mass communication media. The focus of the study includes the vision, mission, supporting factors, and obstacles in attracting audience interest in broadcast programs. This study uses a qualitative method with a descriptive approach. Primary data were obtained through structured interviews with the management and team of Studio eL-TV, as well as direct observation. Secondary data include official documents, archives, and related reference materials. Data analysis techniques include data reduction, data presentation, and verification based on the Miles and Huberman model. The results of the study indicate that Studio eL-TV has succeeded in utilizing digital technology in increasing the effectiveness of information and training delivery. The main supporting factors include support for infrastructure, cooperation with PALTV, and digital-based management. However, the study also found several obstacles, such as limited skilled human resources and variations in program content that are not optimal in attracting a wider audience. This study recommends increasing training for managers, program diversification, and optimizing digital promotion strategies. This study provides theoretical contributions to the study of mass communication based on audiovisual media and is applicable in the management of training-based television studios.